1999
DOI: 10.1071/pp98072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the aluminium-induced root growth inhibition in isolation from low pH effects in Glycine max, Pisum sativum and Phaseolus vulgaris

Abstract: The interaction between proton and aluminium toxicities was examined in soybean (Glycine max L.), pea (Pisum sativum L.) and bean (Phaseolus vulgaris L.). Accurate characterization of genotype Al-sensitivity in solution culture experiments, employing a continuous Al-exposure, required response definition at both growth-enhancing and growth inhibiting activities. Essentially, this involved multiple controls to account for the interactive effects. Experiments measuring growth during a recovery period in Al-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 43 publications
3
28
0
4
Order By: Relevance
“…1a). This is in agreement with Lazof and Holland (1999), who clearly showed the high proton sensitivity of two common bean genotypes. They concluded that screening bean for Al resistance is not possible at pH 4.05 and proposed to evaluate recovery from Al stress as indicator of Al resistance.…”
Section: Adaptation Of the Basal Incubation Medium Used For Maize To supporting
confidence: 80%
See 1 more Smart Citation
“…1a). This is in agreement with Lazof and Holland (1999), who clearly showed the high proton sensitivity of two common bean genotypes. They concluded that screening bean for Al resistance is not possible at pH 4.05 and proposed to evaluate recovery from Al stress as indicator of Al resistance.…”
Section: Adaptation Of the Basal Incubation Medium Used For Maize To supporting
confidence: 80%
“…The relative sensitivity to protons of three legume species increased in the order Pisum sativum < Glycine max < Phaseolus vulgaris (16%-65% inhibition of root elongation, respectively) when the pH of the nutrient solution was reduced from 6.0 to 4.05 (Lazof and Holland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, a strong interaction between Al ions and H+ has been reported among maize cultivars (Llugany et ai. 1995) and crop plant species (Lazof and Holland 1999). Stimulation of growth or elongation of roots at low pH in the presence of Al ions often observed (Mullette 1975;Konishi et ai.…”
mentioning
confidence: 99%
“…With cell cycles at the root meristem of about 18 to 24 h (Gunning and Steer, 1996), it is unlikely that decreased cell division could be responsible for the rapid decreases in root extension occurring within the 1st h of Al exposure (Jones and Kochian, 1995;Llugany et al, 1995;Sivaguru et al, 1999). Nonetheless, a substantial growth inhibition extending over periods of hours or days would have to be associated with decreased cell production (Lazof and Holland, 1999).…”
mentioning
confidence: 99%